1970
DOI: 10.2307/1935375
|View full text |Cite
|
Sign up to set email alerts
|

Plant Communities and Associated Soil and Water Factors of Shale‐Derived Soil in Northeastern Montana

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Sites on different strata of Bearpaw shale and on alluvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Slopes show signs of sheet and gullying erosion, with over 90% of the surface made up of exposed soil. A similar vegetation association has been described by Branson et al (1970) in Valley County and by Vanderhorst et al (1998) for Garter Gounty; both of their studies indicated acid shales as the determinant of the unusual and depauperate vegetation. The examples from the literature occurred on gently rolling terrain whereas this type was only represented on steep slopes on the RNA.…”
Section: Stipa Comata -Bouteloua Gracilis -Carex Fiufoua Herbaceous Vsupporting
confidence: 81%
See 1 more Smart Citation
“…Slopes show signs of sheet and gullying erosion, with over 90% of the surface made up of exposed soil. A similar vegetation association has been described by Branson et al (1970) in Valley County and by Vanderhorst et al (1998) for Garter Gounty; both of their studies indicated acid shales as the determinant of the unusual and depauperate vegetation. The examples from the literature occurred on gently rolling terrain whereas this type was only represented on steep slopes on the RNA.…”
Section: Stipa Comata -Bouteloua Gracilis -Carex Fiufoua Herbaceous Vsupporting
confidence: 81%
“…This localized and small patch association is found on the island's uppermost outcrops and has been previously described in the Limber Pine RNA, in Valley County(Branson et al 1970) and in Carter County(Vanderhorst et al 1998). Soils of this site possess no horizons and are weathered from a very dark grey, possibly acidic, shale and bentonite.…”
supporting
confidence: 75%
“…Roseana was derived directly from a wild collection taken in southeast Montana (USDA-SCS, 1984). Western wheatgrass is moderately tolerant of saline conditions (Branson et al, 1970). Each of the 24 soil samples was represented by three replicates, with all samples from each site planted together in a block of six 5 × 5 × 10 cm cells.…”
Section: Bioassay Experimentsmentioning
confidence: 99%
“…Branson et al (1970) used soil moisture stress in distinguishing plant communities of Willow Creek basin, Montana. They compared the forests on the basis of climatic data, emphasizing especially the ratio of PEjP which is an inverse measure of effective moisture.…”
Section: Discussionmentioning
confidence: 99%